THE ANALYSIS OF READING INTEREST BY FIFTH SEMESTER STUDENTS AT TIDAR UNIVERSITY - Riadil, Ikrar Genidal (Universitas Borneo Tarakan, 2021)
This research decomposes with Teaching English as a Foreign Language (TEFL) of readinginterest by fifth-semester students in class skill one of English Department at Tidar University.This research to identify how much the reading interest of students in class skill one of EnglishDepartment at Tidar University, so the teacher can know how to develop and maintain the readinginterest of their students rightly in reading activity especially reading English material. Thisresearch applies a descriptive qualitative method which used a questionnaire to build this research.